Upper Limb Spasticity: Efficacy and Safety Evaluation of Botulinum Toxin and GAS Usefulness – Retrospective Study - Serrano, Simão; Interno de formação específica de Medicina Física e de Reabilitação - Serviço de Medicina Física e de Reabilitação - Centro Hospitalar e Universitário de Coimbra, Portugal. (2014)
Objectives: To evaluate clinical and functional responses to botulinum toxin type A (BoNT-A) administration in the treatment of upper limb (UL) focal spasticity.Methods: Descriptive, inferential, retrospective study of all patients followed in tonus disorders consultation due to spasticity sequelar to brain injury, treated with BoNT-A, in the last 3 years. Clinical data were collected prior to BoNT-A treatment and on the last observation (≥ 4 weeks after treatment). Goal Attainment Scaling (GAS) was used primarily on the results evaluation and were used secondarily: Visual Analog Scale for pain (VAS), Modified Ashworth Scale (MAS), Goniometry and Likert scale about subjective benefit impression (patient and doctor). Statistical data analysis was performed using Epi Info ™ and IBM SPSS Statistics for Wilcoxon and student’s t tests application.Results: A sample of 28 patients was studied (19 men, 9 women; mean age 55,5 years). We found higher frequencies of: in pathology, ischemic stroke (60,7%); in disability, left hemiplegia (67,9%); and on spasticity patterns, clenched fist and elbow flexion (57,1%). GAS mean was 37,7 (sd=1,1) pre-treatment and 48,5 (sd=3,8) after treatment, with mean increase of 10,8 points (p <0,001). In tonus assessment there was a 0,6 degrees reduction in MAS (0-4) in the elbow (p <0,001), 0,8 in the wrist (p <0,001) and 0,6 in the fingers (p = 0,001). In terms of joint range of motion a gain was found in active and passive movement: +26,4° (p=0,004) and +19,3° (p=0,005) in shoulder abduction, +10,0° and +2,0° in elbow flexion; +3,9º and +4,5º in elbow extension and +3,6° (p=0,006) and 22,5° (p=0,001) in wrist extension, respectively.Conclusions: Results suggest that BoNT-A treatment is effective in reducing upper limb spasticity and range of motion. GAS proved to be a useful and sensitive tool, with the majority of patients achieving the minimum goals initially outlined. Most of the patients had an impression of benefit from BoNT-A application.